Attitude Toward Behavior, Subjective Norms, and Perceived Behavioral Control as Determinants of Accounting Students’ Career Decision-Making in the Digital Era - Surani Dwi Astuti; Dhany Efita Sari (Didaktika: Jurnal Kependidikan, 2025)
The digital era requires accounting education students to develop technological competence, analytical abilities, and self-confidence in making career choices. Nevertheless, many students continue to experience uncertainty in their career decisions due to limited understanding and the influence of social environments. This research aims to examine the effects of attitude toward behavior, subjective norms, and perceived behavioral control on the career decision-making of accounting education students at Universitas Muhammadiyah Surakarta, based on the Theory of Planned Behavior (TPB). Using a quantitative approach with a survey method was applied, and the data were analyzed using multiple regression through SmartPLS 3. The findings show that perceived behavioral control strongly predicts students’ career decision-making, with a path coefficient of 0.473 (p < 0.000), followed by attitude toward behavior with a coefficient of 0.422 (p < 0.000). In contrast, the effect of subjective norms is relatively weak, although still statistically significant, with a path coefficient of 0.095 (p < 0.030), indicating that social influences play a limited role compared to personal and cognitive factors. Collectively, the three variables explain 76.9% (Adjusted R² = 0.761) of the variance in students’ career decision-making, emphasizing that both internal and external factors jointly shape their choices. Overall, the results underscore the necessity of strengthening students’ competencies, technological adaptability, and digital self-confidence as primary factors influencing the career decision-making process. The practical implications suggest that higher education institutions should design curricula and career development programs aimed at enhancing students’ readiness to navigate the evolving labor market.